Influence of dose and duration of smoking on lung cancer rates. - Peto, R (1986)
Lung cancer risks depend far more strongly on the duration than on the daily dose-rate of cigarette smoking. For example, a three-fold increase in the daily dose-rate may produce only about a three-fold increase in effect, while a three-fold increase in duration might produce about a 100-fold increase in effect. Hence, a few decades after cigarette smoking becomes widespread, national lung cancer rates may remain very misleadingly low, even though they will eventually become extremely high.